Information sharing between family and friend carers of older adults and healthcare professionals: Protocol for a systematic review of qualitative studies - Steven Hall; Allison Cammer; Stephanie Chamberlain; Kelly Baskerville; Cavan Fani; Ziyu Li; Hannah M. O’Rourke (PLoS ONE, 2026)
Background Population aging worldwide continues to intensify the demand for family and friend carers to support older adults. Informal carers have long identified information gaps as a key challenge in their caregiving role, underscoring the importance of effective communication and collaboration with healthcare professionals (HCPs). Objectives To complete a comprehensive review of qualitative research and to synthesize what is known about the barriers and facilitators to information sharing between carers of older adults and HCPs. Methods This protocol outlines a systematic review that follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and PRISMA-P 2015 guidelines. We searched MEDLINE, EMBASE, CENTRAL, CINAHL, and PsycINFO on May 5, 2025. Our goal is to identify qualitative studies that meet our “PICo” (Population, phenomena of Interest, Context) eligibility criteria. Population includes carers and HCPs. Phenomena of interest is information sharing between the two populations. Context is carers who provide care to older adults aged 60 or above in any care setting. Two reviewers will independently screen titles and abstracts and full texts. We will use Covidence Extraction 2.0 for extraction of data from included records. Qualitative data from included records will be synthesized using Lockwood’s meta-aggregation and Sandelowski’s meta-summary approach to describe the experiences of information sharing reported within the literature. Discussion By comprehensively evaluating barriers and facilitators to information sharing within the literature, this review will offer significant insights into supporting more effective communication between carers and HCPs. Findings will inform the development of new strategies designed to optimize communication processes between carers and HCPs, with the ultimate goal of improving outcomes for older adults requiring caregiving support. This synthesis of current evidence will also identify gaps for further investigation and underscore the need for innovative communication solutions in diverse healthcare contexts. Trial registration PROSPERO CRD420250636906